Strain Influences the Hydrogen Evolution Activity and Absorption Capacity of Palladium. (14th May 2020) - Jansonius, Ryan P.; Schauer, Phil A.; Dvorak, David J.; MacLeod, Benjamin P.; Fork, David K.; Berlinguette, Curtis P.
Abstract: Strain engineering can increase the activity and selectivity of an electrocatalyst. Tensile strain is known to improve the electrocatalytic activity of palladium electrodes for reduction of carbon dioxide or dioxygen, but determining how strain affects the hydrogen evolution reaction (HER) is complicated by the fact that palladium absorbs hydrogen concurrently with HER. We report here a custom electrochemical cell, which applies tensile strain to a flexible working electrode, that enabled us to resolve how tensile strain affects hydrogen absorption and HER activity for a thin film palladium electrocatalyst. When the electrodes were subjected to mechanically‐applied tensile strain, the amount of hydrogen that absorbed into the palladium decreased, and HER electrocatalytic activity increased. This study showcases how strain can be used to modulate the hydrogen absorption capacity and HER activity of palladium. Abstract : Tensile strain increases the hydrogen evolution reaction rate and decreases hydrogen absorption at a palladium surface. A custom electrochemical cell is reported that applies tensile strain to a flexible working electrode, thus enabling the effect of tensile strain on hydrogen absorption and HER activity for a thin film palladium electrocatalyst to be resolved.